Efficient reduction of peak_to_average power ratio in multiple_input multiple_output orthogonal frequency_division multiplexing system by shuffling cluster sequences - Si Sar Mi; Tanairat Mata; Pornpawit Boonsrimuang; Pisit Boonsrimuang (My University, 2024)
Abstract We propose a shuffling cluster sequence technique without separate side information (SI) for multiple‐input multiple‐output (MIMO) orthogonal frequency‐division multiplexing (OFDM) systems. In the proposed technique, the active subcarriers over two consecutive OFDM symbols are divided into clusters, and each cluster (packet frame) includes a header for ID#cluster and payload for . The clusters are shuffled to reduce the peak‐to‐average power ratio (PAPR) of the time‐domain OFDM signal, which includes the information data and SI signals, with a low computational complexity. At the receiver, the information data can be correctly reconstructed by ID#cluster in the header of each cluster, achieving a smaller bit error rate than the conventional MIMO‐OFDM system without PAPR reduction. Moreover, our technique is comparable with the conventional partial transmit sequence technique without the impact of a separate SI signal even when increasing the number of transmitter antennas in a nonlinear multipath fading channel.
Keywords: Header; Shuffling; Payload (computing); PAPR reduction in OFDM